Development of analytical method for fipronil determination using Gas Chromatography Triple Quadrupole Mass Spectrometry (Asian-Australasian Journal of Food Safety and Security, 2023)
The application of fipronil for the control of insect pests of different crops is increasing day by day. As a result, it is inevitable to remain residues of fipronil in the treated crops. Therefore, it is an urgent need to develop analytical method for the quantification of fipronil. Keeping this view, this study was initiated to develop and optimize an analytical method for the quantification of fipronil residue using Gas Chromatography triple quadrupole Mass Spectrometry (GC-MS/MS). A number of experiments has been conducted to select the parent ion and precusor ion and based on these findings, the analytical method for the determination of fipronil residue using GC-MS/MS was developed. The linearity of the developed analytical method was very good and it was 0.999. The optimization of MS/MS parameters has been done properly through direct injection of 100 ug/L standard solution of fipronil.Asian Australas. J. Food Saf. Secur. 2023, 7 (1), 40-46